Evaluation of the Volleyball Development Program at the Bakung Hoktong Volleyball Club - Agnes Aprilia Kimku; Dewi Septaliza (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This research aims to evaluate the volleyball game training development program at the Bakung Hoktong Palembang club. The method used in this research is the CIPP Model because the CIPP Model is a complex evaluation which includes Context, Input, Process and Product. Evaluation research was carried out from October 2023 to December 2023. Data collection techniques used interviews, questionnaires, observation and documentation. The data analysis technique uses descriptive analysis. The results of the research show that: 1) Evaluation of the contextual aspect obtained a percentage score of 81%, indicating a very good score, meaning that the planning background for the volleyball development program at the Bakung Hoktong Volleyball Club, Palembang, is in the good category. 2) Evaluation of the input aspect obtained a percentage score of 86%, indicating a very good score, meaning that the facilities/model/materials and strategic plans determined to achieve the educational objectives at the Bakung Hoktong Palembang Volleyball Club are in the good category. 3) Evaluation of the process aspects obtained a percentage score of 85% indicating a very good score, meaning that the implementation of coaching and use of facilities is in accordance with what has been planned as well as the strategy and use of facilities/models/materials in activities on the field at the Bakung Hoktong Palembang Volleyball Club in the category good. 4) Evaluation of product aspects obtained a percentage score of 88%, indicating a very good score, meaning that the results achieved in the implementation of coaching (from all coaching) at the Bakung Hoktong Palembang Volleyball Club were in the good category.